2017
DOI: 10.13189/ujer.2017.050302
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Pre-service Mathematics Teachers' Teaching Strategy Knowledge of Geometric Formulas

Abstract: The purpose of this study is to analyze the teaching strategies of the prospective teachers of mathematics for elementary school in relevance with the geometry formulas. The participants of the study are constituted by six senior students of the program of mathematics teaching for elementary school. In this study, where the qualitative research approach is employed, the method of case study is used and the data of the study were aggregated with the techniques of semi-structured interview, observation and analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Moreover, it was realized that the prospective teachers were not able to manage the problem-solving activities successfully and some of their explanations might have resulted in misconceptions or learning difficulties. On this basis, these findings of the study are in line with the conclusions of other studies in the literature stating that teachers or prospective teachers could make explanations seemingly causing misconceptions or learning difficulties and this may be due to their own field knowledge, learning difficulties, or misconceptions (Ball et al 2005;Koçak & Soylu, 2017) because a good teaching strategy knowledge requires good field knowledge first (Loewenberg Ball et al 2008).…”
Section: Conclusion and Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, it was realized that the prospective teachers were not able to manage the problem-solving activities successfully and some of their explanations might have resulted in misconceptions or learning difficulties. On this basis, these findings of the study are in line with the conclusions of other studies in the literature stating that teachers or prospective teachers could make explanations seemingly causing misconceptions or learning difficulties and this may be due to their own field knowledge, learning difficulties, or misconceptions (Ball et al 2005;Koçak & Soylu, 2017) because a good teaching strategy knowledge requires good field knowledge first (Loewenberg Ball et al 2008).…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…Therefore, it is essential to observe the prospective teachers' teaching strategy use in a real-life classroom environment in order to get valid results about their teaching strategy knowledge (Hersey, 2018). In the previous studies, it is seen that researchers mostly studied in environments that do not resemble a real-life classroom to evaluate prospective teachers' teaching strategy knowledge (Batur & Balcı, 2013;Creager, 2016;Didiş Kabar & Amaç, 2018;Koçak & Soylu, 2017;Kind & Chan, 2019;Kuennen & Beam, 2020), and the number of studies conducted in real life classroom settings, that is in primary or secondary school environments, is limited (Jackson et al, 2020;Speer et al, 2015;Wang, 2017). The current study differs from these studies from this aspect, for it was carried in real-life school contexts, which are officially operated by the Ministry of Education [MNE] and so it is significant in terms of providing valid and reliable results about the prospective teachers' teaching strategy knowledge.…”
Section: Figure 1 the Network Of Pedagogical Content Knowledgementioning
confidence: 99%
“…This research has found students' difficulty when solving logarithm problem because trying to apply logarithm formula, but in actually it is not needed, student can not understand the context of the problem and lack motivation about why he uses the properties of logarithm such as what the purpose, is the properties could bring him to the answer? Similar results were obtained from research conducted by Olkun et al, (2014) in today's education, students memorize the mathematical formulas and therefore obtain difficulty in the solution of the problems requiring formula, and teachers teach based on memorization, without emphasizing the sense and rationale of the formula, also the pre-service teacher is not on the part of making the formula be memorized when teaching the formula to which he/she can provide meaning but makes students straightforwardly memorize the formula to which he/she cannot present a meaning (Koçak & Soylu, 2017). It is advantageous to remember the properties of logarithms as long as we know how they are proved, it is also recommended by Esra & Şükrü (2017) if the teacher involves in the mental process of the rational rule explanations hidden in each subject, understanding would be easier.…”
Section: Figure 3 Student's 3 Answermentioning
confidence: 99%
“…From this point of view, prospective mathematics teachers should firstly interpret mathematical formulae and should have knowledge about the fitness for purpose of the formulae they use to be able to teach mathematical formulae to their students. When the literature was examined in this context, studies on prospective teachers' skills of interpreting mathematical formulae were found to be limited (Arslan Kılcan, 2006; Koçak & Soylu, 2017). It was also observed that most of the studies on the interpretation of mathematical formulae and rules were related to students (Barrantes & Blanco, 2006;Battista & Clements, 1996;Doğan, 2001;Olkun, 2003;Kamii & Kysh, 2006 In this context, in this study, it was aimed to examine prospective elementary mathematics teachers' skills of interpreting algebraic formulae they use.…”
Section: Introductionmentioning
confidence: 99%